Impact of land reform on sustainable land management in Ukraine - Roman Kuryltsiv; Józef Hernik; Nadiia Kryshenyk (Acta Scientiarum Polonorum. Formatio Circumiectus, 2018)
The paper describes the current conditions, process, and consequences of the land reform in Ukraine, and goes on to determine their impact on the support for sustainable land management. The research reveals the importance of land development as the main instrument for sustainable land management in Ukraine, which should involve implementation of land policy, organization of rational use and protection of land, land improvement, crop-engineering, and anti-erosion measures. In the present paper, we argue for the measures of sustainable management, which are secured by the development of the programs of land organization, and we present technical and economic reasoning for the use and protection of land in administrative-territorial units, land development projects, as well as environmental and economic arguments for crop rotation and land management, implemented within work projects of land organization at regional, provincial and local levels. Structural instability of the establishment of agrarian formations of a new type, which are basically grounded in the fundamentals of land lease, is caused by a permanent delay on the moratorium for the sale of land parcels by the owners of land shares. It forces most of those owners to engage in economic activity without any pre-existing projects of land organization, which would provide ecologically safe organization of the leased land exploitation. Nowadays, the use of the leased land parcels, and growing of agricultural crops on those parcels, is performed mainly according to the market conjuncture and without any management methods, which would be necessary for securing land protection and maintaining soil fertility.